2003
DOI: 10.1098/rsbl.2003.0076
|View full text |Cite
|
Sign up to set email alerts
|

Efficient utilization of very dilute aquatic sperm: sperm competition may be more likely than sperm limitation when eggs are retained

Abstract: Fertilization success may be severely limited in marine invertebrates that spawn both male and female gametes. In a diverse group of aquatic organisms only sperm are released, with sperm-egg fusion occurring at the mother. Here, we report fertilization kinetics data for two such 'brooding' or 'spermcast' species-representing each major clade of the animal kingdom. High levels of fertilization were achieved at sperm concentrations of two or three orders of magnitude lower than is common with broadcast spawning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 18 publications
4
59
0
Order By: Relevance
“…Meidel & Yund (2001) found that sea urchin eggs had higher fertilization rates when they were able to 'time average' over 24 h of naturally occurring spawning events. The effect of time averaging is further magnified among species that actively pump water past eggs, and a number of studies have shown that tunicates can achieve high fertilization rates even when ambient sperm density is low (Bishop 1998, Pemberton et al 2003.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meidel & Yund (2001) found that sea urchin eggs had higher fertilization rates when they were able to 'time average' over 24 h of naturally occurring spawning events. The effect of time averaging is further magnified among species that actively pump water past eggs, and a number of studies have shown that tunicates can achieve high fertilization rates even when ambient sperm density is low (Bishop 1998, Pemberton et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Meidel & Yund (2001) found that sea urchin eggs had higher fertilization rates when they were able to 'time average' over 24 h of naturally occurring spawning events. The effect of time averaging is further magnified among species that actively pump water past eggs, and a number of studies have shown that tunicates can achieve high fertilization rates even when ambient sperm density is low (Bishop 1998, Pemberton et al 2003.The expectation that large, nearby males will dominate the paternity of larvae on any single colony initially appears intuitive. However, the random success of males that occurred within an area of at least 400 m 2 suggests otherwise and has important implications for our understanding of reproductive systems.…”
mentioning
confidence: 99%
“…Concerns about the fertilization consequences of rapid sperm dilution with distance from sperm source have led to an ongoing debate about the extent to which fertilization in these systems is limited by sperm availability (reviewed in Levitan & Petersen 1995, Yund 2000. In general, egg brooders that possess mechanisms to filter dilute sperm from the water appear to be less sperm-limited than egg broadcasters (Bishop 1998, Yund 2000, Pemberton et al 2003, Johnson & Yund 2004, Phillippi et al 2004. However, experimental approaches that incorporate life history adaptations that minimize gamete dilution effects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Free-spawning marine invertebrates reproduce sexually by releasing sperm into the water, with fertilization occurring either externally (egg broadcasters) or internally (egg brooders, or spermcasters sensu Pemberton et al 2003). Evaluating the physical and biological conditions under which eggs are successfully fertilized is important for understanding the population dynamics of free-spawners.…”
Section: Introductionmentioning
confidence: 99%
“…In sessile marine benthic invertebrates, the encounter between mating partners may be limited when broadcast gametes are exposed to wastage (Yund 1990, Yund & McCartney 1994. In broadcast spawning species in which sperm and eggs are released into the seawater, the rates of fertilization commonly vary between 0 and 100% (Levitan 1995, Pemberton et al 2003. Since fertilization success and mating distance in these species depend on the chance of intersection between sperm and eggs, the species should spawn synchronously to assure fertilization and to avoid the loss of sperm through dilution (e.g.…”
Section: Introductionmentioning
confidence: 99%